Reduced expression of the RNA-binding protein HuD in pancreatic neuroendocrine tumors correlates with low p27Kip1 levels and poor prognosis - Kim, Chongtae; Jeong, Da Eun; Heo, Sungeun; Ji, Eunbyul; Rho, Jun Gi; Jung, Myeongwoo; Ahn, Sojin; Kim, Ye Jin; Kim, Yong Sung; Nam, Suk Woo; Kulkarni, Rohit N.; Lee, Kyoung Bun; et al. (Journal of Pathology, 2018)
For the majority of patients diagnosed with pancreatic neuroendocrine tumors (NETs), there is significant malignant potential with a poor prognosis; however, the molecular abnormalities and pathogenesis of pancreatic NETs have not been firmly established. Here, we report that loss of expression of the RNA-binding protein HuD correlates with low p27Kip1 (p27) levels and poor prognosis in pancreatic NETs. HuD expression was frequently lost in many human pancreatic NETs, and these pancreatic NETs showed aggressive clinicopathological phenotypes with low p27 levels, increased tumor size, higher World Health Organization grade and pT stage of the tumor, and the presence of angioinvasion. Furthermore, loss of HuD was an independent, progression-free prognostic factor in multivariate survival analysis. However, the level of HuR, a member of the same Hu protein family as HuD, was not significantly correlated with pancreatic NET size and progression. Mechanistically, HuD enhanced p27 mRNA translation by interacting with both the 5′-untranslated region (UTR) and the 3′-UTR of p27 mRNA, and consequently suppressed cell cycle progression and tumor growth. In addition, HuD competed with miR-30a-3p for binding to the 3′-UTR of p27 mRNA, suggesting an interplay between HuD and miR-30a-3p in controlling p27 translation. Our results identify HuD as a pivotal suppressor of pancreatic NET growth, and suggest that HuD has potential value as a prognostic factor of pancreatic NETs. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Keywords: 3' Untranslated Regions; 5' Untranslated Regions; Adult; Aged; Animals; Binding Sites; Biomarkers, Tumor; Carcinoma, Neuroendocrine; Cell Cycle; Cell Line, Tumor; Cell Proliferation; Cyclin-Dependent Kinase Inhibitor p27; Down-Regulation; ELAV-Like Protein 4; Female; Gene Expression Regulation, Neoplastic; Humans; Male; Mice, Inbred BALB C; Mice, Knockout; MicroRNAs; Middle Aged; Pancreatic Neoplasms; Phenotype; Progression-Free Survival; Receptor, Insulin; Signal Transduction; Time Factors; Tumor Burden; HuD; p27Kip1; pancreatic neuroendocrine tumor; prognosis; RNA-binding protein